Pan-genome analyses identify lineage- and niche-specific markers of evolution and adaptation in Epsilonproteobacteria - Zhang, Ying; Sievert, Stefan M. (Frontiers in Microbiology, 2014)
The rapidly increasing availability of complete bacterial genomes has created new opportunities for reconstructing bacterial evolution, but it has also highlighted the difficulty to fully understand the genomic and functional variations occurring among different lineages. Using the class Epsilonproteobacteria as a case study, we investigated the composition, flexibility, and function of its pan-genomes. Models were constructed to extrapolate the expansion of pan-genomes at three different taxonomic levels. The results show that, for Epsilonproteobacteria the seemingly large genome variations among strains of the same species are less noticeable when compared with groups at higher taxonomic ranks, indicating that genome stability is imposed by the potential existence of taxonomic boundaries. The analyses of pan-genomes has also defined a set of universally conserved core genes, based on which a phylogenetic tree was constructed to confirm that thermophilic species from deep-sea hydrothermal vents represent the most ancient lineages of Epsilonproteobacteria. Moreover, by comparing the flexible genome of a chemoautotrophic deep-sea vent species to 1) genomes of species belonging to the same genus, but inhabiting different environments, and 2) genomes of other vent species, but belonging to different genera, we were able to delineate the relative importance of lineage-specific versus niche-specific genes. This result not only emphasizes the overall importance of phylogenetic proximity in shaping the variable part of the genome, but also highlights the adaptive functions of niche-specific genes. Overall, by modeling the expansion of pan-genomes and analyzing core and flexible genes, this study provides snapshots on how the complex processes of gene acquisition, conservation, and removal affect the evolution of different species, and contribute to the metabolic diversity and versatility of Epsilonproteobacteria.